การพัฒนาข้าวสายพันธุ์แท้โดยเทคนิดดับเบิลแฮพลอยด์ - โสภณ บุญธรรม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Rice breeding has been employed for the best varieties that high yielding, good grain quality, diseases and insects resistant are noted. Generally conventional breeding has been used by most breeders to create such varieties. However, in order to accomplishthis this goal, the pure line is required and usually it takes not less than 7-8 generations of selfing to obtain. An alternative way to produce pure line is to employ either anther or ovary culture for producing haploid (n=x) and double haploid (2n=2x) in rice. This process can produce homozygous line and rapid fixed recombination. It consumes less time and achievement. The ovaries and anthers of 10 backcross lines (BC3F6) of a cross Rathu Heenati/KDML 105 and 2 backcross lines (BC4F3) of a cross Rathu Heenati/KDML 105//Chai Nat 1 were cultured for callus induction. The results showed that calli from all lines of anther induced callus when cultured on N6 medium supplemented with 2 mg/L NAA, 2 mg/L 2,4-D, 3 mg/L kinetin, 500 mg/L casein hydrolysate and 50 g/L maltose, which gave the highest percentage of calli induction (16.23 and 15.67% from 325(3)-(1) and 237(4)-(1) lines, respectively). The highest percentage of calli induction (10.85%) from the ovary culture was obtained when cultured on N6 medium supplemented with 2 mg/L NAA, 2 mg/L 2,4-D, 1 mg/L kinetin, 500 mg/L casein hydrolysate and 40 g/L maltose. The calli from anther and ovary were regenerated to green plantlet on MS medium supplemented with 2 mg/L BAP, 0.5 mg/L NAA, 500 mg/L casein hydrolysate and 30 g/L sucrose. The percentage of calli development from ovary (7.46%) was greater than anther (3.75%) on same medium. Three and five plants derived from anther and ovary culture respectively were selected and proved to be haploid using chromosome counting, guard cell size, chloroplast number in the guard cell and plant height.